2023
DOI: 10.1371/journal.pone.0291921
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA as a potential diagnostic biomarker in head and neck squamous cell carcinoma: A systematic review and meta-analysis

Mahdi Masrour,
Shaghayegh Khanmohammadi,
Parisa Fallahtafti
et al.

Abstract: Background Head and neck squamous cell carcinoma (HNSCC) is a group of malignancies arising from the epithelium of the head and neck. Despite efforts in treatment, results have remained unsatisfactory, and the death rate is high. Early diagnosis of HNSCC has clinical importance due to its high rates of invasion and metastasis. This systematic review and meta-analysis evaluated the diagnostic accuracy of lncRNAs in HNSCC patients. Methods PubMed, ISI, SCOPUS, and EMBASE were searched for original publications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…The detection of blood sample lncRNAs indicated higher diagnostic accuracy than lncRNAs extracted from BMMC, with an AUC value of 0.95 versus 0.85. Consistently, different studies reported higher diagnostic accuracy for blood‐based samples (serum and plasma) 43,48 . Circulating lncRNAs can be identified easily in serum, plasma, whole blood, urine, and other body fluids 23,24 .…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The detection of blood sample lncRNAs indicated higher diagnostic accuracy than lncRNAs extracted from BMMC, with an AUC value of 0.95 versus 0.85. Consistently, different studies reported higher diagnostic accuracy for blood‐based samples (serum and plasma) 43,48 . Circulating lncRNAs can be identified easily in serum, plasma, whole blood, urine, and other body fluids 23,24 .…”
Section: Discussionmentioning
confidence: 68%
“…Consistently, different studies reported higher diagnostic accuracy for blood‐based samples (serum and plasma). 43 , 48 Circulating lncRNAs can be identified easily in serum, plasma, whole blood, urine, and other body fluids. 23 , 24 On the contrary, different studies showed higher diagnostic performance of lncRNAs from serum samples than plasma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various types of RNAs have recently been applied as a biomarker for disease detection, 7 , 8 but still, there are scarce specified diagnostic panels. Identifying shared lncRNA dysregulation may lend insight into the early patient's diagnosis and prognosis and find potentially novel targets for treatment.…”
Section: Introductionmentioning
confidence: 99%